Interleukin-1α Is a Central Regulator of Leukocyte-Endothelial Adhesion in Myocardial Infarction and in Chronic Kidney Disease. Issue 11 (14th September 2021) - Schunk, Stefan J.; Triem, Sarah; Schmit, David; Zewinger, Stephen; Sarakpi, Tamim; Becker, Ellen; Hütter, Gregor; Wrublewsky, Selina; Küting, Fabienne; Hohl, Mathias; Alansary, Dalia; Prates Roma, Leticia; et al.
Abstract : Background: Cardiovascular diseases and chronic kidney disease (CKD) are highly prevalent, aggravate each other, and account for substantial mortality. Both conditions are characterized by activation of the innate immune system. The alarmin interleukin-1α (IL-1α) is expressed in a variety of cell types promoting (sterile) systemic inflammation. The aim of the present study was to examine the role of IL-1α in mediating inflammation in the setting of acute myocardial infarction (AMI) and CKD. Methods: We assessed the expression of IL-1α on the surface of monocytes from patients with AMI and patients with CKD and determined its association with atherosclerotic cardiovascular disease events during follow-up in an explorative clinical study. Furthermore, we assessed the inflammatory effects of IL-1α in several organ injury models in Il1a −/ − and Il1b −/ − mice and investigated the underlying mechanisms in vitro in monocytes and endothelial cells. Results: IL-1α is strongly expressed on the surface of monocytes from patients with AMI and CKD compared with healthy controls. Higher IL-1α surface expression on monocytes from patients with AMI and CKD was associated with a higher risk for atherosclerotic cardiovascular disease events, which underlines the clinical relevance of IL-1α. In mice, IL-1α, but not IL-1β, mediates leukocyte-endothelial adhesion as determined by intravital microscopy. IL-1α promotes accumulation of macrophages and neutrophils in inflamed tissue in vivo. Furthermore, IL-1α on monocytes stimulates their homing at sites of vascular injury. A variety of stimuli such as free fatty acids or oxalate crystals induce IL-1α surface expression and release by monocytes, which then mediates their adhesion to the endothelium via IL-1 receptor-1. IL-1α also promotes expression of the VCAM-1 (vascular cell adhesion molecule-1) on endothelial cells, thereby fostering the adhesion of circulating leukocytes. IL-1α induces inflammatory injury after experimental AMI, and abrogation of IL-1α prevents the development of CKD in oxalate or adenine-fed mice. Conclusions: IL-1α represents a key mediator of leukocyte-endothelial adhesion and inflammation in AMI and CKD. Inhibition of IL-1α may serve as a novel anti-inflammatory treatment strategy. Abstract : Supplemental Digital Content is available in the text.